Transformasi Paradigma Tafsir Al-Qur'an dari Tekstualisme Klasik menuju Kontekstualisme Kontemporer dalam Studi Islam - Hidayatullah, Rasyid; Syafir, Alsyfidhi Anggrina; Dasuki, Akhmad (Eshraq: Journal of Islamic Studies, 2026)
This article examines the paradigmatic transformation of Qur'anic interpretation from classical textualist approaches toward contemporary contextualist ones as an epistemological phenomenon in modern Islamic studies. The dominance of classical tafsīr methodology, rooted in transmitted authority (naqlī) and linguistic analysis (lughawī), is assessed to have undergone a crisis of relevance when confronted with social, political, and cultural issues of the 20th and 21st centuries. This study employs a qualitative method with a library research approach through critical analysis of primary and secondary sources in the Islamic tafsīr tradition. The findings indicate that this paradigmatic shift is not linear-evolutionary but dialectical, marked by tensions between textual authority and contextual demands, generating new tafsīr methodologies that draw upon hermeneutics, social sciences, and historical-critical approaches. The contributions of Fazlur Rahman, Muhammad Arkoun, and Nasr Hamid Abu Zayd serve as concrete representations of this methodological transformation. The article concludes that contextualism is not a rejection of the text, but an expansion of tafsīr epistemology that acknowledges the dynamic relationship between text, historical context, and the interpreter's subjectivity in contemporary Islamic studies.